Analisis Keselamatan dan Kesehatan Kerja (K3) dengan Metode HAZOP (Hazard and Operability Study) Pada Pekerja Buruh Bongkar TBS di PT. Karya Agung Sawita - Padang Lawas Sumatera Utara - Doni Syaputra Hasibuan; Irmayani I; Isna Juwita (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze occupational safety and health (OSH) among workers unloading fresh fruit bunches (FFB) at PT. Karya Agung Sawita, Padang Lawas, North Sumatra, using the Hazard and Operability Study (HAZOP) method. The main hazards identified in the workplace include non-ergonomic work postures, slippery floors scattered with fruit scraps, and unsafe procedures for opening truck rear doors. This study employed a quantitative descriptive method using observation, interviews, documentation, and questionnaires involving 32 respondents. The data were analyzed using a HAZOP worksheet to identify hazards, deviations, causes, consequences, and control measures. The results identified three main sources of hazards, namely work posture, floor conditions, and truck door opening procedures, with extreme, high, and moderate risk levels. The implementation of the OSH program was categorized as sufficient, with a normalized average score of 70.58%. The study recommends ergonomic training, the use of personal protective equipment (PPE), regular cleaning of work areas, and the implementation of safe truck door opening procedures to improve workplace safety and productivity.